Influence of Financial Literacy and Financial Technology on Financial Inclusion in the Use of Dana Digital Payment Services (Case Study on Students of the University of Bengkulu) - Elvionita, Melinia; Zoraya, Intan (Universitas Bengkulu, 2024)
This research aims to determine the influence of financial literacy and financial technology on the level of financial inclusion with the research object DANA digital payments among Bengkulu University students. This research is quantitative and uses proportional sampling techniques and stratified random sampling. The population in this study were active D3 and S1 students at Bengkulu University, totaling 390 respondents. The data analysis technique uses multiple linear regression analysis using IBM SPSS 26.0 software. The results of this research show that financial literacy influences financial inclusion. Meanwhile, financial technology does not influence financial inclusion.